1990
DOI: 10.1042/bj2680219
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-based inactivation of monoamine oxidases A and B by tetrahydropyridines and dihydropyridines

Abstract: I-Methyl-4-phenyl-1 ,2,3,6-tetrahydropyridine (MPTP) and its primary oxidation product, l-methyl-4-phenyl-2,3-dihydropyridinium (MPDP+), are mechanism-based inhibitors of monoamine oxidases A and B. The pseudo-first-order rate constants for inactivation were determined for various analogues of MPTP and MPDP+ and the concentrations in all redox states were measured throughout the reaction. Disproportionation was observed for all the dihydropyridiniums, but non-enzymic oxidation was insignificant. The dihydropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
(45 reference statements)
1
9
0
Order By: Relevance
“…Similar results were obtained using 4'-alkyl-MPP ÷ analogs to protect NADH dehydrogenase from inhibition by and binding of rotenone [48,49]. A logical extension of these studies, now in progress in our laboratory, will be the identification of the peptide involved in binding these inhibitors, using photoaffinity labeling with 4'-azido-3[H]MPP ÷ .…”
Section: Identification Of the Binding Site On Nadh Dehydrogenasesupporting
confidence: 56%
See 2 more Smart Citations
“…Similar results were obtained using 4'-alkyl-MPP ÷ analogs to protect NADH dehydrogenase from inhibition by and binding of rotenone [48,49]. A logical extension of these studies, now in progress in our laboratory, will be the identification of the peptide involved in binding these inhibitors, using photoaffinity labeling with 4'-azido-3[H]MPP ÷ .…”
Section: Identification Of the Binding Site On Nadh Dehydrogenasesupporting
confidence: 56%
“…All but the nheptyl and n-decyl analog nevertheless dissociate on dilution, so that they may be completely removed by centrifugation and washing of submitochondrial particles, with resultant recovery of the activity, whereas piericidin A remains firmly (but non-covalently) bound at the specific site during such treatment, and rotenone dissociates only partly during several cycles of centrifugation and resuspension in sucrose-serum albumin. This difference in the dissociation of the enzymeinhibitor complexes permitted the demonstration that MPP ÷ analogs prevent the binding of rotenone and of piericidin A to NADH dehydrogenase and thus protect the enzyme from their powerful inhibitory effect [48,49]. Fig.…”
Section: Identification Of the Binding Site On Nadh Dehydrogenasementioning
confidence: 98%
See 1 more Smart Citation
“…Second, the extracellular levels of MPDP+ remained quite stable throughout the 4 days of incubation of astrocytes in the presence of MPTP. Previous studies have shown that at relatively low concentrations of MPDP+ M) non-enzymic oxidation to MPP+ occurs, while disproportionation of MPDP+ to MPTP and MPP+ is negligible (Krueger et al, 1990;Singer et al, 1986). Extracellular concentrations of MPDP+ in astrocyte cultures exposed to MPTP were in the lop6 M range; therefore, the lack of accumulation of the unstable molecule of MPDP+ in the culture medium is likely to be due to its autoxidation, which forms MPP+.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of MPTP by MAO also proved interesting at the molecular level. Not only were there two oxidative steps in the process, first to MPDP + and then to MPP + , but the intermediates in the reaction could inactivate the enzyme [99][100][101].…”
Section: Mao Is a Metabolic Enzymementioning
confidence: 99%